2019
DOI: 10.1146/annurev-psych-010418-102753
|View full text |Cite
|
Sign up to set email alerts
|

Face Processing in Infancy and Beyond: The Case of Social Categories

Abstract: Prior reviews of infant face processing have emphasized how infants respond to faces in general. This review highlights how infants come to respond differentially to social categories of faces based on differential experience, with a focus on race and gender. We examine six different behaviors: preference, recognition, scanning, category formation, association with emotion, and selective learning. Although some aspects of infant responding to face race and gender may be accounted for by traditional models of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
68
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 156 publications
(217 reference statements)
2
68
0
Order By: Relevance
“…Indeed, past research has found that people tend to form more accurate impressions of people who share their ethnic background (Rogers & Biesanz, ). Interestingly, this finding could be driven by attentional engagement given that people tend to prefer looking at similar others (e.g., individuals of the same gender or ethnicity; Quinn, Lee, & Pascalis, ). Thus, future research could examine whether perceived similarity for in‐group members increases attentional engagement to targets and therefore to impression accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, past research has found that people tend to form more accurate impressions of people who share their ethnic background (Rogers & Biesanz, ). Interestingly, this finding could be driven by attentional engagement given that people tend to prefer looking at similar others (e.g., individuals of the same gender or ethnicity; Quinn, Lee, & Pascalis, ). Thus, future research could examine whether perceived similarity for in‐group members increases attentional engagement to targets and therefore to impression accuracy.…”
Section: Discussionmentioning
confidence: 99%
“…For example, human and NHP newborns orient more toward faces and face‐shaped patterns compared to other images (Bard, Platzman, Lester, & Suomi, 1992; Kuwahata, Adachi, Fujita, Tomonaga, & Matsuzawa, 2004; Paukner, Bower, Simpson, & Suomi, 2013; Simpson et al., 2017; Valenza, Simion, Cassia, & Umiltà, 1996). These social preferences persist as infants develop (Sifre et al., 2018), while also becoming specialized for familiar categories, such as primary caretakers’ species, race, and gender (Quinn, Lee, & Pascalis, 2019; Scott & Fava, 2013). These social sensitivities appear evolutionarily conserved across primates and emerge early in development, shaped by infants’ social experiences (Simpson, Maylott, Lazo, et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…For example, at birth, infants can differentiate among individuals of various races. By 3 months, however, those raised in racially homogeneous contexts become less able to differentiate among members of unfamiliar races, perceiving that they all look and sound alike (Perrachione, Chiao, & Wong, 2010; Quinn, Lee, & Pascalis, 2019). As another example, individuals raised in relatively collectivistic contexts often focus on others, whereas those raised in relatively individualistic contexts often focus on themselves, which can give rise to racial differences in memory construction and recall (Wang, 2019; Wang, Song, & Koh, 2017).…”
mentioning
confidence: 99%